CK1/Doubletime activity delays transcription activation in the circadian clock - Deniz Top; Jenna L O'Neil; Gregory E Merz; Kritika Dusad; Brian R Crane; Michael W Young (eLife, 2018)
In the Drosophila circadian clock, Period (PER) and Timeless (TIM) proteins inhibit Clock-mediated transcription of per and tim genes until PER is degraded by Doubletime/CK1 (DBT)-mediated phosphorylation, establishing a negative feedback loop. Multiple regulatory delays within this feedback loop ensure ~24 hr periodicity. Of these delays, the mechanisms that regulate delayed PER degradation (and Clock reactivation) remain unclear. Here we show that phosphorylation of certain DBT target sites within a central region of PER affect PER inhibition of Clock and the stability of the PER/TIM complex. Our results indicate that phosphorylation of PER residue S589 stabilizes and activates PER inhibitory function in the presence of TIM, but promotes PER degradation in its absence. The role of DBT in regulating PER activity, stabilization and degradation ensures that these events are chronologically and biochemically linked, and contributes to the timing of an essential delay that influences the period of the circadian clock.